Supraglottic airway devices are associated with asphyxial physiology after prolonged CPR in patients with refractory Out-of-Hospital cardiac arrest presenting for extracorporeal cardiopulmonary resuscitation. (May 2023) - Bartos, Jason A.; Clare Agdamag, Arianne; Kalra, Rajat; Nutting, Lindsay; Frascone, R.J.; Burnett, Aaron; Vuljaj, Nik; Lick, Charles; Tanghe, Peter; Quinn, Ryan; Simpson, Nicholas; Peterson, Bjorn; et al.
Abstract: Background: Multiple randomized clinical trials have compared specific airway management strategies during ACLS with conflicting results. However, patients with refractory cardiac arrest died in almost all cases without the availability of extracorporeal cardiopulmonary resuscitation (ECPR). Our aim was to determine if endotracheal intubation (ETI) was associated with improved outcomes compared to supraglottic airways (SGA) in patients with refractory cardiac arrest presenting for ECPR. Methods: We retrospectively studied 420 consecutive adult patients with refractory out-of-hospital cardiac arrest due to shockable presenting rhythms presenting to the University of Minnesota ECPR program. We compared outcomes between patients receiving ETI ( n  = 179) and SGA ( n  = 204). The primary outcome was the pre-cannulation arterial PaO2 upon arrival to the ECMO cannulation center. Secondary outcomes included neurologically favorable survival to hospital discharge and eligibility for VA-ECMO based upon resuscitation continuation criteria applied upon arrival to the ECMO cannulation center. Results: Patients receiving ETI had significantly higher median PaO2 (71 vs. 58 mmHg, p  = 0.001), lower median PaCO2 (55 vs. 75 mmHg, p  < 0.001), and higher median pH (7.03 vs. 6.93, p  < 0.001) compared to those receiving SGA. Patients receiving ETI were also significantly more likely to meet VA-ECMO eligibility criteria (85% vs. 74%, p  = 0.008). Of patients eligible for VA-ECMO, patients receiving ETI had significantly higher neurologically favorable survival compared to SGA (42% vs. 29%, p  = 0.02). Conclusions: ETI was associated with improved oxygenation and ventilation after prolonged CPR. This resulted in increased rate of candidacy for ECPR and increased neurologically favorable survival to discharge with ETI compared to SGA.